2017
DOI: 10.4103/aer.aer_82_17
|View full text |Cite|
|
Sign up to set email alerts
|

Intrathecal hyperbaric bupivacaine with varying doses of buprenorphine for postoperative analgesia after cesarean section: A comparative study

Abstract: Background:Postoperative analgesia after cesarean section poses unique clinical challenges to anesthesiologist. Intrathecal buprenorphine is a promising drug for postoperative analgesia.Aim:The aim of this study was to compare the efficacy of two doses of buprenorphine (45 μg and 60 μg) as an adjuvant to hyperbaric bupivacaine for postoperative analgesia in cesarean section.Setting and Design:Prospective randomized double-blind controlled study involving ninety parturients posted for elective cesarean section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…However, when morphine is also added to the intrathecal mixture, fentanyl might induce acute opioid tolerance and result in greater opioid consumption [59]. Intrathecal buprenorphine [60] and epidural hydromorphone [61] resulted in improved postoperative analgesia and reduced opioid consumption compared with intrathecal bupivacaine or ropivacaine alone.…”
Section: Resultsmentioning
confidence: 99%
“…However, when morphine is also added to the intrathecal mixture, fentanyl might induce acute opioid tolerance and result in greater opioid consumption [59]. Intrathecal buprenorphine [60] and epidural hydromorphone [61] resulted in improved postoperative analgesia and reduced opioid consumption compared with intrathecal bupivacaine or ropivacaine alone.…”
Section: Resultsmentioning
confidence: 99%
“…Opioids are still currently being used as adjuvants to intrathecal blocks as side effects are minimal, and they can be safely used in the elderly as well as pregnant patients and ease of availability makes them a practical choice. [ 17 18 19 20 21 22 23 24 25 26 27 ] Previous systematic reviews have evaluated the safety and efficacy of intrathecal opioids (Fentanyl) as adjuvants for spinal anesthesia. [ 17 18 19 ] A study conducted by Wang and et al on the effects of intrathecal bupivacaine and bupivacaine plus fentanyl in elderly patients undergoing total hip arthroplasty showed that although the quality of anesthesia was the same, the fentanyl group showed less use of ephedrine for stable hemodynamics and a longer duration for postoperative analgesic use.…”
Section: Discussionmentioning
confidence: 99%
“…Its high lipid solubility, higher affinity for opioid receptors, and long duration of action make it a better choice as postoperative analgesic. [2] Dexmedetomidine is a highly selective α 2 adrenoceptor agonist that binds eight times more avidly to α 2 receptors than clonidine having sympatholytic, sedative-hypnotic, anxiolytic, and analgesic property. [3]…”
Section: Introductionmentioning
confidence: 99%